KONSELING KELUARGA MELALUI PENDEKATAN SPIRITUAL ISLAMI DAN IMPLEMENTASI TEORI DALAM KONSELING - Rahman, Fadhila; Nafisah, Syifa Jauhar (JIEGC Journal of Islamic Education Guidance and Counselling, 2021)
Islamic spiritual counseling is based on views about God, human nature, the purpose of life, spirituality, morality, and life after death. Spiritual counseling is done by praying techniques, teaching spiritual concepts, scripture references, spiritual experiences, praying, encouraging forgiveness and using religious communities or groups. The research was conducted qualitatively using case studies in order to be described in depth and to understand the life and problems of the subject. Sampling used purposive sampling which experienced problems and needed counseling treatment through spiritual techniques. Collecting data using interview and assessment methods. The results of the study indicate that the client has been able to adapt well in managing problems and shows a commitment to solving these problems.